The Web system of structured documentation - Kunth, Donald E. (1983)
since Web is an experimental system developed for internal use within the TEX project at Stanford, this report is rather terse, and it assumes that the reader is an experienced programmer who is highly motivated to read a detailed description of WEB rules. Further more, even if a less terse manual were to be written, the WEB must be familer with both TEX and PASCAL. when one writes of WEB and/ or rules of TEX and/ or the rules of PASCAL. In practice, all three types of error will occur, and you will get different error messages from the different language processors. In compensation for the sophisticated expertise needed to cope with such a variety of languages, however, experience has shown that reliable software can e created quite rapidly by working entirely in WEB form the beginning; and the documentation of such programs seems to be better than the documentation obtained by any other known method. Thus, WEB users need to highly qualified, but they can get some satisfaction and perhaps even a spacial feeling of accomplishment when they have successfully created a software system with this method.
Introduction -- The Character set -- Input and Output -- Reporting errors to the user -- Data structures -- Searching for identifiers -- Initializing the table of reserved words -- Searching for moiled names -- Lexical scanning -- Inputting the next token -- Phase one processing -- Low- Level output routines -- Routines that copy TEX material -- Parsing -- Implementation the production -- Initializing the scraps -- Output of tokens -- Phase two processing -- Phase three processing -- Debugging -- The main Program -- System- dependent changes
Includes index and appendix
Keywords: Computer Programming; Web system; Structured documentation